IMPACT OF COVID-19 PANDEMIC ON THE RADIOTHERAPY AND CANCER PATIENTS IN A TERTIARY HEALTH CARE CENTER OF ASSAM, NORTHEAST INDIA: A RETROSPECTIVE SINGLE INSTITUTION STUDY - Baruah, C.; Deka, K.; Paul, T.; Sarma, B.; Patowary, P.; Sreeni, S.; Mahanta, B. (International Journal of Medicine and Medical Research, 2023)
Background. The COVID-19 pandemic has affected every sector of health care system including the cancer care. Objective. The purpose of the study is to analyse the impact of the current COVID‑19 pandemic on routine radiotherapy practice at a tertiary hospital of Northeast India. Methods. This is a retrospective study of all patients planned for radiotherapy at Assam Medical College, a tertiary care centre, in Assam, India from January 1, 2020 to May 31, 2020. The study samples are divided into two groups: group A – patients treated from January 1, 2020, to March 20, 2020 (pre-lockdown,) and group B – patients treated from March 21, 2020, to May 31, 2020 (lockdown). The department registration numbers of all the patients were collected from the entry register, and the respective paper files were then accessed to obtain the required data. Results. A total of 153 patients were planned for radiotherapy during the study period, of these 113 patients receiving radiotherapy in the pre-lockdown period and 40 patients receiving it in the lockdown period. The number of female patients decreased from 66 (58.40%) in the pre-lockdown period to 20 (50%) during the lockdown. The number of male patients also decreased from 47 to 20 but the proportion increased from 41.5% to 50%. The proportion of patients who completed radiotherapy was 90.8% in group B compare to 88.3% in group A. Conclusion. There was a decrease in number of cancer patients, especially female during the lockdown. The pandemic has severely disrupted every aspect of cancer care.